Implementación de la Mediación Intrajudicial en delitos menores a 5 años contra la propiedad como medio de Justicia restaurativa - Ramón Guamán, María Victoria (2023)
This degree thesis entitled "IMPLEMENTATION OF INTRAJUDICIAL MEDIATION IN CRIMES LESS THAN 5 YEARS AGAINST PROPERTY AS A MEANS OF RESTORATIVE JUSTICE" entails a detailed analysis of the feasibility of this alternative to be incorporated into the Ecuadorian regulatory framework, within the Code Comprehensive Criminal Law, as an adequate and valid mechanism to solve conflicts in crimes of less than five years against property, the amount of which does not exceed thirty unified basic wages of the worker in general. This investigation began with the evaluation of the main principles that underlie the criminal process, such as those of minimal intervention, legal security and criminal guarantee, due to their notable gravitation at the time of making decisions, especially when punitiveness is not applied according to to an appropriate proportionality according to the crime committed. The search for alternative means that transcend custodial sentences is necessary, therefore, they seek to generate new horizons in criminal matters. It is here, when Restorative Justice becomes a pioneer, by offering viable, humane and effective solutions, due to the excellent results achieved in criminal mediation, where the victim, as well as the person who commits the crime, are positively affected in the criminal proceedings, by guaranteeing the full validity of fundamental principles, such as voluntariness, confidentiality, flexibility and neutrality, with the participation of an impartial third party, who through dialogue between the parties, has managed to resolve the conflict, in an appropriate manner. and convenient. This indisputable effectiveness, demonstrated by the perfectible but successful practice that occurs in most European countries and unfortunately in Latin America, is no more than a theoretical reference of distant real application that slowly begins to involve criminal mediation. Here, we are still not able to see beyond the old punitive and inefficient systems, which have caused serious problems in our society, as demonstrated by the high rates of crime, deaths and impunity. Although the path may be long, complex and difficult, it is clear that our current penal system urgently needs to be reformed. Taking into account that positivity has not always been the best solution, especially in the case of crimes against property, the Organic Comprehensive Criminal 5 Code must consider, as a priority, alternative solutions to conciliation, where a neutral third party participates to provide the necessary guidelines for both the victim and the offender. In this way, the present legal research work that deals with criminal mediation within the Ecuadorian Restorative Justice is exposed, for which, a detailed analysis has been carried out about the real viability that exists in the country, to implement this modality. in the case of misdemeanors to five years against property; with the aim of serving as a guide for students and professionals of Law as a source of consultation and knowledge.